PENGARUH LATIHAN TRICEP EKSTENSION DAN LATIHAN LONCAT TALI TERHADAP KEMAMPUAN SMASH DALAM PERMAINAN BOLA VOLI - Ahmad, Ahmad; Satrianingsih, Baiq; Muhaimin, Ali (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
Volleyball is a team game played by two teams whereas each team consists of 6 players (plus a libero player), separated by the net and aiming for each team to pass the ball regularly (each team plays ball maximum 3 times) over the net until the ball touches the floor in the opponent's area. The purpose of this research is to determine the effect of tricep extension exercise and rope jumping exercise toward the smash ability. This research is quantitative research with one group pre-test - post test and the sampling technique uses the proposive random sampling with the samples of 14 players while the test instrument used the smash test of volley ball. The data analysis uses the t-test and the data obtained from the results of the volleyball club in kec.kempo. The data obtained then was analyzed by using SPSS. The result of research showed that the t-score is 6.885 compared to t-table is 1.771 at 5% significance level on degree of freedom N-1 = 14 - 1 = 13. Since the t score> t table (6.885> 1.771) then the alternative hypothesis is accepted so it is concluded that there is an effect of tricep extension exercise and rope jumping exercise toward the smash ability in volleyball Club in Kempo Dompu in 2017/2018. In conclusion, the tricep extension exercises and the rope jumping exercises in a volleyball game is very influential to maximize the smash so it can be concluded that "There is effect of tricep extension exercise and rope jumping exercise toward the smash ability in volleyball.